Architecting Multi-Cloud Immutable Infrastructure Workflows: Beyond Traditional CI/CD - Sridhar Nelloru (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the advanced realm of multi-cloud immutable infrastructure workflows, presenting a comprehensive analysis of their implementation, benefits, and future directions. It delves into the foundational principles of immutable infrastructure and their application in multi-cloud environments, highlighting the integration with Infrastructure as Code and policy-as-code frameworks. The discussion extends to advanced patterns and workflows, including strategies for unifying disparate cloud APIs, leveraging orchestration tools, and standardizing security measures across heterogeneous environments. The article examines how these approaches enhance both stability and agility in software deployment, covering dynamic scaling policies, automated rollback mechanisms, and strategies for maintaining consistency. It also addresses the operational benefits and challenges associated with these workflows, providing insights into faster service deployment, reduced operational overhead, and proactive governance management. Looking ahead, the article forecasts the impact of emerging technologies such as artificial intelligence and machine learning on multi-cloud orchestration and infrastructure management. By offering a holistic view of current practices and future trends, this article serves as a valuable resource for organizations seeking to optimize their cloud infrastructure strategies and stay ahead in the rapidly evolving landscape of software deployment and management.